Experimental verification of parameters in automobile crankshaft modelling for vibration analysis - Pyae, Sanda Sone (2015)
In the interest of utilized more stable automobile components at high speed for reduction the vibration of mechanical system, dynamic characteristics analysis plays a vital role in complex mechanical parts. This paper introduces a clarified approach on statistical investigation and modal analysis methodology to study, predict and accurate crankshaft natural frequencies by using design of experiment (DOE). In this research, first, simulation had been done with MSC Nastran/ Patran to find out the natural frequencies in each mode shape of crankshaft as well as the verification with experiment was carried out. In order to less inaccuracy, numerous simplified crankshaft models were created by using these as input and DOE was established to acquire precise parameters of optimized crankshaft design as the second phase. This method can be further used for the optimizing the structural parameters and would provide some value basis to qualitative measure of parameters and determination of optimized structure. In Conclusion, modal verification accuracy between experimental and simulation has improved.